A phage display approach for rapid antibody humanization: Designed combinatorial V gene libraries - Rader, Christoph (The National Academy of Sciences, 1998)
The development of a new strategy for antibody humanization is described. This strategy incorporates key recognition sequences from the parental rodent antibody into a phage display-based selection strategy. The original sequences of the third complementarity-determining regions (CDRs) of heavy and light chains, HCDR3 and LCDR3, were maintained and all other sequences were replaced by human sequences selected from phage-displayed antibody libraries. This approach was applied to the humanization of mouse mAb LM609 that is directed to human integrin α(v)β(3) and has potential applicability in cancer therapy as an antiangiogenic agent. We demonstrate this approach (i) provides a rapid route for antibody humanization constraining the content of original mouse sequences in the final antibodies to the most hypervariable of the CDRs; (ii) generates several humanized versions with different sequences at the same time; (iii) results in affinities as high as or higher than the affinity of the original antibody; and (iv) retains the antigen and epitope specificity of the original antibody. The production of multiple humanized variants may present advantages in the selection of antibodies that are more readily expressed on a large scale and could be important in therapeutic regimens that call for long-term treatment with antibodies in which antiidiotypic responses might be avoided by administration of alternative antibodies.